2021
DOI: 10.1111/aas.13845
|View full text |Cite
|
Sign up to set email alerts
|

Difference in postoperative opioid consumption after spinal versus general anaesthesia for ankle fracture surgery—A retrospective cohort study

Abstract: Background: Surgical treatment of ankle fracture is associated with significant pain and high postoperative opioid consumption. The anaesthesia method may affect early postoperative pain. The main objective of the study was to compare postoperative opioid consumption after ankle-fracture surgery between patients treated with spinal anaesthesia and general anaesthesia. Methods:We reviewed retrospectively the files of 586 adult patients with surgically treated ankle fracture in the years 2014 through 2016. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Christensen et al [10] found that, compared with general anesthesia alone, general anesthesia plus peripheral adductor/popliteal nerve block (difference: -15.0 OME [95% CI -25.8 to -3.9]; p < 0.01) and spinal anesthesia with (difference: -21.0 OME [95% CI -31.5 to -10.2]; p < 0.01) or without (difference: -13.5 OME [95% CI -24.3 to -2.7]; p = 0.01) adductor/popliteal nerve block was associated with less opioid consumption over 24 hours. Similarly, Lehto et al [28] also found that spinal anesthesia was associated with fewer OMEs during the first 48 hours postoperatively (difference: -41.1 [95% CI -56.4 to -25.5]; p < 0.001) compared with general anesthesia. Kruse et al [26] reported that time of tourniquet use was linearly associated with increased opioid use (slope: 0.12 OMEs/min [95% CI 0.06 to 0.21]).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Christensen et al [10] found that, compared with general anesthesia alone, general anesthesia plus peripheral adductor/popliteal nerve block (difference: -15.0 OME [95% CI -25.8 to -3.9]; p < 0.01) and spinal anesthesia with (difference: -21.0 OME [95% CI -31.5 to -10.2]; p < 0.01) or without (difference: -13.5 OME [95% CI -24.3 to -2.7]; p = 0.01) adductor/popliteal nerve block was associated with less opioid consumption over 24 hours. Similarly, Lehto et al [28] also found that spinal anesthesia was associated with fewer OMEs during the first 48 hours postoperatively (difference: -41.1 [95% CI -56.4 to -25.5]; p < 0.001) compared with general anesthesia. Kruse et al [26] reported that time of tourniquet use was linearly associated with increased opioid use (slope: 0.12 OMEs/min [95% CI 0.06 to 0.21]).…”
Section: Resultsmentioning
confidence: 83%
“…After exclusions, 18 articles were included (Fig. 1) [6,8,10,12,14,15,18,20,25,26,28,31,38,41,42,47,51,54]. Two studies were randomized controlled trials, whereas the remainder were observational.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations